India in a changing Arctic: an appraisal - Pareek, Nikhil (Ecocycles, 2020)
In the complex undercurrents of evolving new great power politics, the scheme of Arctic affairs make for a low key affair. India in Arctic is a theme which is so inconsequential that it fails to even grab a mention. The performance of observer states in the Arctic affairs has varied substantially during these years but Indian attempts have remained short of the promise. There is immense possibility for India to build on her non hegemonic, non intrusive foreign policy approach to obtain a greater role in the in this strategically vital and economically lucrative region.